سوء استخدام المكتبات المدرسية الحكومية من قبل طالبات الثانوية العامة بمدينة البيضاء - عبدالسلام عبدالله حنان (مجلة كلية الاداب, 2024)
Libraries play the role of the school's lifeblood by providing educational resources that teachers and educators rely on. The current study aims to identify the forms of misuse to which school libraries are exposed, and to identify the policies of the libraries under study in dealing with various forms of misuse. The problem of the current research lies in highlighting the importance of these libraries, and the negative impact that their absence has on the abilities and skills of students in secondary schools. This is due to the misuse of these skills, and the current study revolves around girls’ secondary school students in the city of Al-Bayda, and librarians in these schools, in the period 2021/2022 AD.